Houston, Chloë. The Renaissance Utopia: Dialogue, Travel and the Ideal Society. Farnham: Ashgate, 2014. 198 pp. - Maczelka, Csaba (FOCUS: Papers in English Literary and Cultural Studies, 2014)
The title of Chloë Houston’s recent monograph on Renaissance utopia does not only hint at some of the main trends within utopian studies in the past decades, but it might also remind the reader of a 1980s classic on 16th-17th-century English utopian writing. The link is further reinforced by an explicit reference to the same in the blurb on the back of the volume, where the book advertises itself as “the first comprehensive attempt since J. C. Davis’ Utopia and the Ideal Society to understand the societies projected by [early modern] utopian literature.” Marginal as such a text is to the whole volume, this short note epitomizes how the volume constantly struggles to find its place within the two main poles of utopian studies: the study of “societies projected” and “utopian literature.”